Criterion for convexity of a domain of a Euclidean space - Vyhovs'ka, I. Yu.; Zelinskii, Yu. B.; Выговская, И. Ю.; Зелинский, Ю. Б.; Выговская, И. Ю.; Зелинский, Ю. Б. (Institute of Mathematics, NAS of Ukraine, 2008)
We establish an external criterion for the convexity of a domain of a Euclidean space.